Talent Management in Emerging Market Firms Global Strategy and Local Challenges - Latukha, Marina (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Investigating talent management in firms from emerging economies, this book discusses strategies and practices of managing talented employees in the context of BRIC countries. Talent Management in Emerging Market Firms illustrates how emerging multinationals use their talent management to create and extend competitive advantage in global markets, and how they support their competition with talent as their main asset. Extending the talent management perspective, the book compares companies from Brazil, Russia, India and China to provide the link between talent management practices, a firm's performance and organizational competitiveness within the context of emerging economies.